A Solution with Ginseng Saponins and Selenium as Vaccine Diluent to Increase Th1/Th2 Immune Responses in Mice - Yong Wang; Xuemei Cui; Lijia Yuan; Babar Maqbool; Wei Xu; Shanshan He; Ran Guan; Songhua Hu (Journal of Immunology Research)
Pseudorabies is an important infectious disease of swine, and immunization using attenuated pseudorabies virus (aPrV) vaccine is a routine practice to control this disease in swine herds. This study was to evaluate a saline solution containing ginseng stem-leaf saponins (GSLS) and sodium selenite (Se) as a vaccine adjuvant for its enhancement of immune response to aPrV vaccine. The results showed that aPrV vaccine diluted with saline containing GSLS-Se (aP-GSe) induced significantly higher immune responses than that of the vaccine diluted with saline alone (aP-S). The aP-GSe promoted higher production of gB-specific IgG, IgG1, and IgG2a, neutralizing antibody titers, secretion of Th1-type (IFN-γ, IL-2, IL-12), and Th2-type (IL-4, IL-6, IL-10) cytokines, and upregulated the T-bet/GATA-3 mRNA expression when compared to aP-S. In addition, cytolytic activity of NK cells, lymphocyte proliferation, and CD4+/CD8+ ratio was also significantly increased by aP-GSe. More importantly, aP-GSe conferred a much higher resistance of mice to a field virulent pseudorabies virus (fPrV) challenge. As the present study was conducted in mice, further study is required to evaluate the aP-GSe to improve the vaccination against PrV in swine.